Prevalence of Escherichia coli O157:H7 in cow-calf herds in Kansas - J.M. Sargeant; J.R. Gillespie; D.R. Hyatt; J.C. Galland; L.K. Bohra; Richard D. Oberst; Randall K. Phebus; Michael P. Hays (Kansas Agricultural Experiment Station Research Reports, 1998)
Fecal samples from cows and calves and samples of water sources were collected monthly for 8 months from 10 Kansas cow-calf farms to determine the prevalence of E. coli O157:H7. The bacterium was found in 8% of fecal samples from cows that were within 24 hours of calving, 1.4% of fecal samples from cows which were not within 24 hours of calving, 1.4% of calf fecal samples, and 1.5% of water samples. E. coli O157:H7 was identified from at least one sample on all farms.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen& #x27; s Day; 1998; Beef; Cow-calf herds; E. coli O157:H7; Bacterial infection